The Effect of Size and Working Fluid on the Multi-Objective Design of High-Speed Centrifugal Compressors. (November 2022) - Giuffre, Andrea; Colonna, Piero; Pini, Matteo
Highlights: The development and validation of a model for single-stage centrifugal compressors is presented The influence of fluid and size on efficiency, operating range, and axial thrust on bearings is investigated The results are presented in the form of design maps Design maps are generated for six working fluids and different values of size parameter The multi-objective optimization of a compressor stage for a heat pump application is documented Abstract: The impact of size and working fluid on the efficiency, operating range, and axial thrust on bearings is examined for high-speed, oil-free centrifugal compressors. First, the development and validation of a reduced-order model based on scaling principles is documented. Then, the validated compressor model is used to generate design maps for stages operating with arbitrary fluid molecules, and characterized by different size. The results show that compressors operating with fluids made by heavy and complex molecules provide lower efficiency over the entire design space, if compared to their simple-molecule counterparts. However, compressors for complex-molecule fluids require lower rotational speed, and generate lower axial thrust on bearings, thus making them particularly suitable for small-scale applications. Furthermore, a decreasing value of the size parameter has a detrimental effect on the stage efficiency, as a result of manufacturing constraints. The results computed by the compressor model suggest that the efficiency penalty is more sensitive to variations of clearance gap than to surface finishing. Lastly, the reduced-order model has been used to perform a design exercise, i.e., the multi-objective optimization of the first compressor stage of the heat pump test rig being realized at Delft University of Technology. The key characteristics of the optimal compressor design has been compared to those derived from the design maps, to corroborate their validity. The optimal design has been extensively characterized by means of CFD, providing further evidence that efficient mini-compressors operating with organic fluids, and featuring pressure ratios up to five at off-design, are feasible.